Data Descriptor: Daily observations of stable isotope ratios of rainfall in the tropics - Munksgaard, Niels C.; Kurita, Naoyuki; Sanchez-Murillo, Ricardo; Ahmed, Nasir; Araguas, Luis; Balachew, Dagnachew L.; Bird, Michael I.; Chakraborty, Supriyo; Nguyen Kien Chinh; Cobb, Kim M.; Ellis, Shelby A.; Esquivel-Hernandez, Germain; et al. (Nature Publishing Group, 2019)
We present precipitation isotope data (delta H-2 and delta O-18 values) from 19 stations across the tropics collected from 2012 to 2017 under the Coordinated Research Project F31004 sponsored by the International Atomic Energy Agency. Rainfall samples were collected daily and analysed for stable isotopic ratios of oxygen and hydrogen by participating laboratories following a common analytical framework. We also calculated daily mean stratiform rainfall area fractions around each station over an area of 5 degrees x 5 degrees longitude/latitude based on TRMM/GPM satellite data. Isotope time series, along with information on rainfall amount and stratiform/convective proportions provide a valuable tool for rainfall characterisation and to improve the ability of isotope-enabled Global Circulation Models to predict variability and availability of inputs to fresh water resources across the tropics.